Impact of E-Learning on Secondary School Students in Nigeria during COVID-19 Lockdown - Adekunle, Soladoye Afeez; Opeyemi, Ojo Adeolu (International Journal of Scientific Research in Computer Science and Engineering, 2021)
Online Instructional Method has become the only way out when the incidence of Covid-19 lockdown put all the world economic and social activities on pause, which led to a stop in academic activities too. Nigeria was not excluded and we need a way to ensure continuation in academics activities of the students, this led to the adoption of E-Learning. This is the very first time the Nigerian Education Sector fully and openly call for adoption of online classes, which made it very hard for many students to adapt easily to it, while some people have problems with digital devices or lack access to good internet network. This study aims to study the level of involvement and participation of secondary school students in Nigeria, the impact this E-Learning has on their studies after the resumption, their view on this method of learning. A survey of 200 secondary school students was randomly selected from four Federal Unity Schools across Nigeria, Google form was used as a means to collect primary data from these students, the link to the form was shared with their teachers for them to fill it in school while some were filled by them in their ICT units/Lab. The collected primary data was analyzed using descriptive analysis, while the mean of some related questions was also analyzed using ANOVA (Analysis of variance) to check maybe there is any significant difference among them and to know maybe the respondents maintain consistency while answering the questions. The findings of this research indicate the level of participation of the 200 randomly selected students which represent the level of participation of the secondary school students at large because all these students come from various parts of the country, it also show that the most used E-learning platform is WhatsApp and that the adoption of E-Learning really helped the students during the covid-19 Lockdown as it kept them busy and able to make good use of the long break and exposed them to the use of digital devices for Learning, while most students are ready to attend online classes if the need arises.